Chikungunya intra-vector dynamics in Aedes albopictus from Lyon (France) upon exposure to a human viremia-like dose range reveals vector barrier’s permissiveness and supports local epidemic potential - Viginier, Barbara; Cappuccio, Lucie; Garnier, Céline; Martin, Edwige; Maisse, Carine; Valiente Moro, Claire; Minard, Guillaume; Fontaine, Albin; Lequime, Sébastian; Ratinier, Maxime; Arnaud, Frédérick; Raquin, Vincent (Peer Community Journal)

(untitled)
Arbovirus emergence and epidemic potential, as approximated by the vectorial capacity formula, depends on host and vector parameters, including the vector’s intrinsic ability to replicate then transmit the pathogen known as vector competence. Vector competence is a complex, time-dependent, quantitative phenotype influenced by biotic and abiotic factors. A combination of experimental and modelling approaches is required to assess arbovirus intra-vector dynamics and estimate epidemic potential. In this study, we measured infection, dissemination, and transmission dynamics of chikungunya virus (CHIKV) in a field-derived Aedes albopictus population (Lyon, France) after oral exposure to a range of virus doses spanning human viraemia. Statistical modelling indicates rapid and efficient CHIKV progression in the vector mainly due to an absence of a dissemination barrier, with 100% of the infected mosquitoes ultimately exhibiting a disseminated infection, regardless of the virus dose. Transmission rate data revealed a time-dependent, but overall weak, transmission barrier, with individuals transmitting as soon as 2 days post-exposure (dpe) and >50% infectious mosquitoes at 6 dpe for the highest dose. Based on these experimental intra-vector dynamics data, epidemiological simulations conducted with an agent-based model showed that even at low mosquito biting rates, CHIKV could trigger outbreaks locally. Together, this reveals the epidemic potential of CHIKV upon transmission by Aedes albopictus in mainland France.